To equate or to leave it different? (Reading gender interpretations in Islamic texts) - Amien, Saiful (2013)
This paper aims to trace evolving interpretations of the Islamic tradition, especially understanding of gender and relationship between men and women used as a basis by Muslim feminists to construct their theological thinking.It focuses on two theologians’ thought, namely Riffat Hassan and Sachiko Murata, considering that both are feminist scholars represent different perspectives and approaches in explaining gender relations, especially the interpretation of two important issues: the concept of creation of women [QS. an-Nisa ': 1], and male-female equality [QS. An-Nisa’: 34].Regarding the creation of women, as represented by the case of Eve, it is part of Muslims’ belief that Eve was created from Adam’s rib.This type of interpretation has long been developed in Islamic tradition.However, this kind of interpretation is totally rejected by Riffat Hassan on the basis that this interpretation could spread misogynistic tendency (hatred of women) and that there is no clear text in the Qur’an which implies such a conclusion.The Qur’an, Hassan posits, only mentions the word "nafs wahidah" (one soul) and "zawjaha" (partner).Therefore, according to Riffat, it is not true if "nafs wahidah" is automatically understood as Adam and "zawjaha" as Eve.Although, many exegetes during this time using Hadith to interpret these two words, Riffat’s study shows that the validity of sanad (transmission lines) and matan (content) of the Hadith was doubtful.In addition to relatively dhoif (weak) transmitters, its contents also bertray the principles of justice and equality prevailed in Islam.In contrast, Sachiko Murata agrees with the interpretation that has evolved. In spite of her great belief to the authority of Mufassirin (Exegetes) who employed bi riwayah interpretation method, Murata also found that there is a batiniyah (spiritual) wisdom behind the creation of Eve from Adam's rib.According to her, there is love to realize the cosmic balance and harmony.Similarly, regarding male-female equality, Murata contends that both must be different (should not be the same) in terms of both sex and gender. Contrastingly, Riffat argues that both males and females should be the same and equal.